A method for preparing photosensitive selective ink

By grafting POSS in epoxy acrylic resin and using corrosion-resistant zinc oxide microcapsules and modified nitrogen-doped carbon nanodots, the problem of insufficient corrosion resistance of photosensitive inks is solved, and the effect of efficiently blocking corrosive media and extending service life of the ink is achieved.

CN118755304BActive Publication Date: 2025-03-25NANXIONG KOTTI CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411061743.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2025-03-25
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

Photosensitive inks are susceptible to chemical corrosion during printing, resulting in insufficient corrosion resistance and short service life.

Method used

By grafting POSS into the epoxy acrylic resin chain segment, the hydrophobicity and hardness of the resin are improved, and nano zinc oxide is used as the wall material and modified nitrogen-doped carbon nanodots are modified as the core material to prepare corrosion-resistant zinc oxide microcapsules, and combined with branched polyethyleneimine to modify nitrogen-doped carbon nanodots, the corrosion resistance of the ink is enhanced.

Benefits of technology

It significantly improves the hydrophobicity and corrosion resistance of the ink, enhances the barrier ability to corrosive media, and extends the service life of the ink.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of ink technology, and specifically to a method for preparing a photosensitive selective ink. The present invention uses nano zinc oxide as a wall material and modified nitrogen-doped carbon nanodots as a core material to prepare a zinc oxide microcapsule. Using ethylenediamine as a nitrogen source, nitrogen elements are doped into carbon nanodots. The nitrogen-doped carbon nanodots have good corrosion resistance and can effectively block the penetration of corrosive media in the ink, so that the ink can better block the erosion of the corrosive media and improve the acid and alkali resistance of the ink. Benzotriazole is also added in the present invention to further improve the corrosion resistance of the ink.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inks, in particular to a method for preparing photosensitive selective ink. Background Art

[0002] With the development of printing technology and the continuous development of application fields, alkali-soluble photosensitive ink, as an important printing material, has been widely used in the fields of packaging printing and electronic display, especially in high-precision printing and flexible electronic technology. Alkali-soluble photosensitive ink is usually composed of photosensitive resin, solvent, filler, binder and various additives. Alkali-soluble photosensitive ink has attracted much attention due to its advantages such as high resolution and rapid solidification. However, photosensitive ink is easily affected by chemical corrosion during the printing process. Therefore, it is crucial to improve the corrosion resistance of ink so that it has long-term stability and long service life in complex environments.

[0003] In order to solve the above problems and improve the corrosion resistance of ink, the present invention provides a method for preparing photosensitive selective ink. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a photosensitive selective ink to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a photosensitive selective ink comprises the following steps:

[0007] Step 1: Take toluene and butyl acetate, stir evenly, heat to 45-50°C, add butyl acrylate, styrene, azobisisobutyronitrile, allyl glycidyl ether, POSS, stir evenly to obtain a mixed solution A; take toluene and butyl acetate, stir evenly, add one-third of the mixed solution A by mass, heat to 80°C, stir for 20-30min, dropwise add the remaining two-thirds of the mixed solution A and thioglycolic acid, keep warm for 4-4.5h, and rotary evaporate to obtain epoxy acrylic resin;

[0008] Step 2: taking an alkali-soluble acrylic resin, acetone, UV monomer, photoinitiator, pigment, corrosion-resistant zinc oxide microcapsule, dispersant, defoamer, and accelerator, and mixing them uniformly to obtain a mixture A;

[0009] Step 3: Take epoxy resin, epoxy acrylic resin, epoxy curing agent, N, N-dimethylbenzylamine, and propylene glycol, mix them evenly to obtain a mixture B;

[0010] Step 4: Mix mixture A and mixture B evenly to obtain photosensitive selective ink.

[0011] More optimally, the preparation method of the corrosion-resistant zinc oxide microcapsules is: take sodium dodecyl sulfate, anhydrous ethanol, and deionized water, stir evenly to obtain a sodium dodecyl sulfate solution; take modified nitrogen-doped carbon nanodots, benzotriazole, anhydrous ethanol, and cyclohexane, stir evenly to obtain a modified nitrogen-doped carbon nanodot solution; add the sodium dodecyl sulfate solution to the modified nitrogen-doped carbon nanodot solution, stir for 15-20 minutes, and obtain a mixed solution; take zinc acetate dihydrate and deionized water, stir evenly to obtain a zinc acetate solution, add the zinc acetate solution dropwise to the mixed solution at 15-17°C, stir for 1-1.5 hours, centrifuge, and wash to obtain corrosion-resistant zinc oxide microcapsules.

[0012] More optimally, the preparation method of the modified nitrogen-doped carbon nanodots is: take nitrogen-doped carbon nanodots and deionized water, mix them evenly, add branched polyethyleneimine, stir at 60-65° C. for 100-120 minutes, and dry to obtain modified nitrogen-doped carbon nanodots.

[0013] More optimally, the preparation method of the nitrogen-doped carbon nanodots is: take 1.2g of monohydrated citric acid powder and 10mL of deionized water, ultrasonically dissolve, add 355μL of ethylenediamine liquid, react at 200°C for 7.5-8.5h, cool and dry to obtain nitrogen-doped carbon nanodots.

[0014] More optimally, the mass ratio of the nitrogen-doped carbon nanodots, branched polyethyleneimine, and deionized water is 0.5:(2-3):10.

[0015] More optimally, the mixture A comprises the following ingredients, by weight: 60-70 parts of alkali-soluble acrylic resin, 20-25 parts of acetone, 10-15 parts of UV monomer, 8-15 parts of photoinitiator, 15-20 parts of pigment, 15-25 parts of corrosion-resistant zinc oxide microcapsules, 1-2 parts of dispersant, 0.1-0.2 parts of defoamer, and 2-3 parts of accelerator.

[0016] More optimally, the mixture B comprises the following components, by weight: 30-40 parts of epoxy resin, 20-30 parts of epoxy acrylic resin, 10-12 parts of epoxy curing agent, 2-5 parts of N,N-dimethylbenzylamine, and 12-20 parts of propylene glycol.

[0017] More preferably, the UV monomer is any one or more of hydroxyethyl (meth)acrylate, isobornyl (meth)acrylate, diethylene glycol diacrylate, hexanediol diacrylate, trimethylol triacrylate, pentaerythritol triacrylate, and dipentaerythritol pentaacrylate;

[0018] The photoinitiator is any one or more of benzophenone, p-phenylbenzophenone, isopropylthioxanthone, and 1-hydroxycyclohexyl phenyl ketone;

[0019] The pigment includes one or more of carbon black, iron blue, ultramarine blue, phthalocyanine blue, titanium dioxide, and bismuth yellow;

[0020] The dispersant includes any one or more of polyethylene glycol, polyacrylate, and sodium oleate;

[0021] The defoaming agent includes any one or more of polydimethylsiloxane and polyoxypropylene oxyethylene glycerol ether;

[0022] The accelerator includes any one or more of 2-methylimidazole, 2-ethylimidazole, and 2-ethyl-4-methylimidazole.

[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0024] (1) The present invention grafts POSS into the epoxy acrylic resin chain segment, thereby improving the hydrophobicity and hardness of the resin and improving the compatibility with the epoxy resin, thereby improving the hydrophobicity and corrosion resistance of the ink.

[0025] (2) The present invention uses nano zinc oxide as the wall material and modified nitrogen-doped carbon nanodots as the core material to prepare a zinc oxide microcapsule. Ethylenediamine is used as the nitrogen source, and nitrogen is doped in the carbon nanodots. The nitrogen-doped carbon nanodots have good corrosion resistance and can effectively block the penetration of corrosive media in the ink, so that the ink can better block the erosion of the corrosive media and improve the acid and alkali resistance of the ink. Benzotriazole is also added in the present invention to further improve the corrosion resistance of the ink.

[0026] (3) The present invention uses branched polyethyleneimine to modify the nitrogen-doped carbon nanodots, so that a large number of amino groups are grafted on the surface of the modified nitrogen-doped carbon nanodots. The amino groups can react with the epoxy groups on the epoxy resin and the epoxy acrylic resin, so that the corrosion-resistant zinc oxide microcapsules are better dispersed in the ink and are not easy to agglomerate, thereby improving the corrosion resistance of the ink. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The purchase manufacturers of all raw materials in the present invention are not particularly limited, and illustratively include: POSS: model: T8 MA / iBu-POSS, which can be purchased from HybridPlastics, USA; alkali-soluble acrylic resin: model: Soluryl70, which can be purchased from Hanwha; epoxy resin: model: E51; epoxy curing agent: model: D230, which can be purchased from Dalian Liansheng Trading Co., Ltd.; branched polyethyleneimine: model: 408727, which can be purchased from Merck; carbon black: particle size 400-500nm.

[0029] Embodiment 1: A method for preparing a photosensitive selective ink, comprising the following steps:

[0030] Step 1: Preparation of epoxy acrylic resin:

[0031] Take 5g toluene and 5g butyl acetate, stir evenly, heat to 47°C, add 16g butyl acrylate, 10.5g styrene, 0.15g azobisisobutyronitrile, 5.8g allyl glycidyl ether, 3.2g POSS, stir evenly to obtain a mixed solution A; take 12.5g toluene and 12.5g butyl acetate, stir evenly, add one-third of the mixed solution A by mass, heat to 80°C, stir for 25min, dropwise add the remaining two-thirds of the mixed solution A and 0.16g of thioglycolic acid, keep warm for 4h, and rotary evaporate to obtain an epoxy acrylic resin;

[0032] Step 2: Preparation of modified nitrogen-doped carbon nanodots:

[0033] Take 1.2 g of monohydrated citric acid powder and 10 mL of deionized water, dissolve them by ultrasonication, add 355 μL of ethylenediamine liquid, react at 200 °C for 8 h, cool and dry to obtain nitrogen-doped carbon nanodots;

[0034] Take 0.5 g of nitrogen-doped carbon nanodots and 10 mL of deionized water, mix them evenly, add 2.5 g of branched polyethyleneimine, stir at 63 ° C for 110 min, and dry to obtain modified nitrogen-doped carbon nanodots;

[0035] The mass ratio of the nitrogen-doped carbon nanodots, branched polyethyleneimine, and deionized water is 0.5:2.5:10;

[0036] Step 3: Preparation of corrosion-resistant zinc oxide microcapsules:

[0037] Take 1.5g of sodium dodecyl sulfate, 150mL of anhydrous ethanol, and 450mL of deionized water, stir evenly to obtain a sodium dodecyl sulfate solution; take 0.5g of modified nitrogen-doped carbon nanodots, 0.7g of benzotriazole, 50mL of anhydrous ethanol, and 3.8g of cyclohexane, stir evenly to obtain a modified nitrogen-doped carbon nanodot solution; add the sodium dodecyl sulfate solution to the modified nitrogen-doped carbon nanodot solution, stir for 18min, and obtain a mixed solution; take 16.5g of zinc acetate dihydrate and 45mL of deionized water, stir evenly to obtain a zinc acetate solution, add the zinc acetate solution dropwise to the mixed solution at 16°C, stir for 1.2h, centrifuge, and wash to obtain corrosion-resistant zinc oxide microcapsules;

[0038] Step 4: Preparation of photosensitive selective ink:

[0039] Alkali-soluble acrylic resin, acetone, UV monomer (meth) acrylate isobornyl, photoinitiator p-phenyl benzophenone, pigment carbon black, corrosion-resistant zinc oxide microcapsules, dispersant polyethylene glycol, defoamer polyoxypropylene oxyethylene glycerol ether, and accelerator 2-ethylimidazole are mixed uniformly to obtain a mixture A; epoxy resin, epoxy acrylic resin, epoxy curing agent D230, N, N-dimethylbenzylamine, and propylene glycol are mixed uniformly to obtain a mixture B; the mixture A and the mixture B are mixed uniformly to obtain a photosensitive selective ink;

[0040] The mixture A comprises the following components, by weight: 65 parts of alkali-soluble acrylic resin, 22 parts of acetone, 12 parts of UV monomer, 12 parts of photoinitiator, 17 parts of pigment, 20 parts of corrosion-resistant zinc oxide microcapsules, 1.5 parts of dispersant, 0.15 parts of defoamer, and 2.5 parts of accelerator;

[0041] The mixture B includes the following components, by weight: 35 parts of epoxy resin, 25 parts of epoxy acrylic resin, 11 parts of epoxy curing agent D230, 3 parts of N,N-dimethylbenzylamine, and 15 parts of propylene glycol.

[0042] Embodiment 2: A method for preparing a photosensitive selective ink, comprising the following steps:

[0043] Step 1: Preparation of epoxy acrylic resin:

[0044] Take 5 g of toluene and 5 g of butyl acetate, stir evenly, heat to 45°C, add 16 g of butyl acrylate, 10.5 g of styrene, 0.15 g of azobisisobutyronitrile, 5.8 g of allyl glycidyl ether, and 3.2 g of POSS, stir evenly to obtain a mixed solution A;

[0045] Take 12.5g toluene and 12.5g butyl acetate, stir evenly, add one-third of the mixed solution A by mass, heat to 80°C, stir for 20min, dropwise add the remaining two-thirds of the mixed solution A and 0.16g of thioglycolic acid, keep warm for 4h, and rotary evaporate to obtain epoxy acrylic resin;

[0046] Step 2: Preparation of modified nitrogen-doped carbon nanodots:

[0047] Take 1.2 g of monohydrated citric acid powder and 10 mL of deionized water, dissolve by ultrasonication, add 355 μL of ethylenediamine liquid, react at 200 °C for 7.5 h, cool and dry to obtain nitrogen-doped carbon nanodots;

[0048] Take 0.5 g of nitrogen-doped carbon nanodots and 10 mL of deionized water, mix them evenly, add 2 g of branched polyethyleneimine, stir at 60 ° C for 100 min, and dry to obtain modified nitrogen-doped carbon nanodots;

[0049] The mass ratio of the nitrogen-doped carbon nanodots, branched polyethyleneimine, and deionized water is 0.5:2:10;

[0050] Step 3: Preparation of corrosion-resistant zinc oxide microcapsules:

[0051] Take 1.5g of sodium dodecyl sulfate, 150mL of anhydrous ethanol, and 450mL of deionized water, stir evenly to obtain a sodium dodecyl sulfate solution; take 0.5g of modified nitrogen-doped carbon nanodots, 0.7g of benzotriazole, 50mL of anhydrous ethanol, and 3.8g of cyclohexane, stir evenly to obtain a modified nitrogen-doped carbon nanodot solution; add the sodium dodecyl sulfate solution to the modified nitrogen-doped carbon nanodot solution, stir for 15 minutes, and obtain a mixed solution; take 16.5g of zinc acetate dihydrate and 45mL of deionized water, stir evenly to obtain a zinc acetate solution, add the zinc acetate solution dropwise to the mixed solution at 15°C, stir for 1h, centrifuge, and wash to obtain corrosion-resistant zinc oxide microcapsules;

[0052] Step 4: Preparation of photosensitive selective ink:

[0053] Alkali-soluble acrylic resin, acetone, UV monomer (meth) hydroxyethyl acrylate, photoinitiator benzophenone, pigment carbon black, corrosion-resistant zinc oxide microcapsules, dispersant polyethylene glycol, defoamer polydimethylsiloxane, and accelerator 2-methylimidazole are mixed evenly to obtain a mixture A; epoxy resin, epoxy acrylic resin, epoxy curing agent D230, N, N-dimethylbenzylamine, and propylene glycol are mixed evenly to obtain a mixture B; the mixture A and the mixture B are mixed evenly to obtain a photosensitive selective ink;

[0054] The mixture A comprises the following components, by weight: 60 parts of alkali-soluble acrylic resin, 20 parts of acetone, 10 parts of UV monomer, 8 parts of photoinitiator, 15 parts of pigment, 15 parts of corrosion-resistant zinc oxide microcapsules, 1 part of dispersant, 0.1 parts of defoamer, and 2 parts of accelerator;

[0055] The mixture B includes the following components, by weight: 30 parts of epoxy resin, 20 parts of epoxy acrylic resin, 10 parts of epoxy curing agent D230, 2 parts of N,N-dimethylbenzylamine, and 12 parts of propylene glycol.

[0056] Embodiment 3: A method for preparing a photosensitive selective ink, comprising the following steps:

[0057] Step 1: Preparation of epoxy acrylic resin:

[0058] Take 5 g of toluene and 5 g of butyl acetate, stir evenly, heat to 50°C, add 16 g of butyl acrylate, 10.5 g of styrene, 0.15 g of azobisisobutyronitrile, 5.8 g of allyl glycidyl ether, and 3.2 g of POSS, stir evenly to obtain a mixed solution A;

[0059] Take 12.5g toluene and 12.5g butyl acetate, stir evenly, add one-third of the mixed solution A by weight, heat to 80°C, stir for 30min, dropwise add the remaining two-thirds of the mixed solution A and 0.16g of thioglycolic acid, keep warm for 4.5h, and rotary evaporate to obtain epoxy acrylic resin;

[0060] Step 2: Preparation of modified nitrogen-doped carbon nanodots:

[0061] Take 1.2 g of monohydrated citric acid powder and 10 mL of deionized water, dissolve by ultrasonication, add 355 μL of ethylenediamine liquid, react at 200 °C for 8.5 h, cool and dry to obtain nitrogen-doped carbon nanodots;

[0062] Take 0.5 g of nitrogen-doped carbon nanodots and 10 mL of deionized water, mix them evenly, add 3 g of branched polyethyleneimine, stir at 65 °C for 120 min, and dry to obtain modified nitrogen-doped carbon nanodots;

[0063] The mass ratio of the nitrogen-doped carbon nanodots, branched polyethyleneimine, and deionized water is 0.5:3:10;

[0064] Step 3: Preparation of corrosion-resistant zinc oxide microcapsules:

[0065] Take 1.5g of sodium dodecyl sulfate, 150mL of anhydrous ethanol, and 450mL of deionized water, stir evenly to obtain a sodium dodecyl sulfate solution; take 0.5g of modified nitrogen-doped carbon nanodots, 0.7g of benzotriazole, 50mL of anhydrous ethanol, and 3.8g of cyclohexane, stir evenly to obtain a modified nitrogen-doped carbon nanodot solution; add the sodium dodecyl sulfate solution to the modified nitrogen-doped carbon nanodot solution, stir for 20min, and obtain a mixed solution; take 16.5g of zinc acetate dihydrate and 45mL of deionized water, stir evenly to obtain a zinc acetate solution, add the zinc acetate solution dropwise to the mixed solution at 17°C, stir for 1.5h, centrifuge, and wash to obtain corrosion-resistant zinc oxide microcapsules;

[0066] Step 4: Preparation of photosensitive selective ink:

[0067] Alkali-soluble acrylic resin, acetone, UV monomer (meth) hydroxyethyl acrylate, photoinitiator benzophenone, pigment carbon black, corrosion-resistant zinc oxide microcapsules, dispersant polyethylene glycol, defoamer polydimethylsiloxane, and accelerator 2-methylimidazole are mixed evenly to obtain a mixture A; epoxy resin, epoxy acrylic resin, epoxy curing agent D230, N, N-dimethylbenzylamine, and propylene glycol are mixed evenly to obtain a mixture B; the mixture A and the mixture B are mixed evenly to obtain a photosensitive selective ink;

[0068] The mixture A comprises the following components, by weight: 70 parts of alkali-soluble acrylic resin, 25 parts of acetone, 15 parts of UV monomer, 15 parts of photoinitiator, 20 parts of pigment, 25 parts of corrosion-resistant zinc oxide microcapsules, 2 parts of dispersant, 0.2 parts of defoamer, and 3 parts of accelerator;

[0069] The mixture B includes the following components, by weight: 40 parts of epoxy resin, 30 parts of epoxy acrylic resin, 12 parts of epoxy curing agent D230, 5 parts of N,N-dimethylbenzylamine, and 20 parts of propylene glycol.

[0070] Comparative Example 1: No epoxy acrylic resin was added, and the rest was the same as Example 1:

[0071] Step 1: Preparation of modified nitrogen-doped carbon nanodots:

[0072] Take 1.2 g of monohydrated citric acid powder and 10 mL of deionized water, dissolve them by ultrasonication, add 355 μL of ethylenediamine liquid, react at 200 °C for 8 h, cool and dry to obtain nitrogen-doped carbon nanodots;

[0073] Take 0.5 g of nitrogen-doped carbon nanodots and 10 mL of deionized water, mix them evenly, add 2.5 g of branched polyethyleneimine, stir at 63 ° C for 110 min, and dry to obtain modified nitrogen-doped carbon nanodots;

[0074] The mass ratio of the nitrogen-doped carbon nanodots, branched polyethyleneimine, and deionized water is 0.5:2.5:10;

[0075] Step 2: Preparation of corrosion-resistant zinc oxide microcapsules:

[0076] Take 1.5g of sodium dodecyl sulfate, 150mL of anhydrous ethanol, and 450mL of deionized water, stir evenly to obtain a sodium dodecyl sulfate solution; take 0.5g of modified nitrogen-doped carbon nanodots, 0.7g of benzotriazole, 50mL of anhydrous ethanol, and 3.8g of cyclohexane, stir evenly to obtain a modified nitrogen-doped carbon nanodot solution; add the sodium dodecyl sulfate solution to the modified nitrogen-doped carbon nanodot solution, stir for 18min, and obtain a mixed solution; take 16.5g of zinc acetate dihydrate and 45mL of deionized water, stir evenly to obtain a zinc acetate solution, add the zinc acetate solution dropwise to the mixed solution at 16°C, stir for 1.2h, centrifuge, and wash to obtain corrosion-resistant zinc oxide microcapsules;

[0077] Step 3: Preparation of photosensitive selective ink:

[0078] Alkali-soluble acrylic resin, acetone, UV monomer (meth) acrylate isobornyl, photoinitiator p-phenyl benzophenone, pigment carbon black, corrosion-resistant zinc oxide microcapsules, dispersant polyethylene glycol, defoamer polyoxypropylene oxyethylene glycerol ether, and accelerator 2-ethylimidazole are mixed uniformly to obtain a mixture A; epoxy resin, epoxy curing agent D230, N, N-dimethylbenzylamine, and propylene glycol are mixed uniformly to obtain a mixture B; the mixture A and the mixture B are mixed uniformly to obtain a photosensitive selective ink;

[0079] The mixture A comprises the following components, by weight: 65 parts of alkali-soluble acrylic resin, 22 parts of acetone, 12 parts of UV monomer, 12 parts of photoinitiator, 17 parts of pigment, 20 parts of corrosion-resistant zinc oxide microcapsules, 1.5 parts of dispersant, 0.15 parts of defoamer, and 2.5 parts of accelerator;

[0080] The mixture B includes the following components, by weight: 60 parts of epoxy resin, 11 parts of epoxy curing agent D230, 3 parts of N,N-dimethylbenzylamine, and 15 parts of propylene glycol.

[0081] Comparative Example 2: No modified nitrogen-doped carbon nanodots were added, and the rest was the same as Example 1:

[0082] Step 1: Preparation of epoxy acrylic resin:

[0083] Take 5g toluene and 5g butyl acetate, stir evenly, heat to 47°C, add 16g butyl acrylate, 10.5g styrene, 0.15g azobisisobutyronitrile, 5.8g allyl glycidyl ether, 3.2g POSS, stir evenly to obtain a mixed solution A; take 12.5g toluene and 12.5g butyl acetate, stir evenly, add one-third of the mixed solution A by mass, heat to 80°C, stir for 25min, dropwise add the remaining two-thirds of the mixed solution A and 0.16g of thioglycolic acid, keep warm for 4h, and rotary evaporate to obtain an epoxy acrylic resin;

[0084] Step 2: Preparation of corrosion-resistant zinc oxide microcapsules:

[0085] Take 1.5g of sodium dodecyl sulfate, 150mL of anhydrous ethanol, and 450mL of deionized water, stir evenly to obtain a sodium dodecyl sulfate solution; take 0.7g of benzotriazole, 50mL of anhydrous ethanol, and 3.8g of cyclohexane, stir evenly to obtain a benzotriazole solution; add the sodium dodecyl sulfate solution to the benzotriazole solution, stir for 18 minutes, and obtain a mixed solution; take 16.5g of zinc acetate dihydrate and 45mL of deionized water, stir evenly to obtain a zinc acetate solution, add the zinc acetate solution dropwise to the mixed solution at 16°C, stir for 1.2 hours, centrifuge, and wash to obtain corrosion-resistant zinc oxide microcapsules;

[0086] Step 3: Preparation of photosensitive selective ink:

[0087] Alkali-soluble acrylic resin, acetone, UV monomer (meth) acrylate isobornyl, photoinitiator p-phenyl benzophenone, pigment carbon black, corrosion-resistant zinc oxide microcapsules, dispersant polyethylene glycol, defoamer polyoxypropylene oxyethylene glycerol ether, and accelerator 2-ethylimidazole are mixed uniformly to obtain a mixture A; epoxy resin, epoxy acrylic resin, epoxy curing agent D230, N, N-dimethylbenzylamine, and propylene glycol are mixed uniformly to obtain a mixture B; the mixture A and the mixture B are mixed uniformly to obtain a photosensitive selective ink;

[0088] The mixture A comprises the following components, by weight: 65 parts of alkali-soluble acrylic resin, 22 parts of acetone, 12 parts of UV monomer, 12 parts of photoinitiator, 17 parts of pigment, 20 parts of corrosion-resistant zinc oxide microcapsules, 1.5 parts of dispersant, 0.15 parts of defoamer, and 2.5 parts of accelerator;

[0089] The mixture B includes the following components, by weight: 35 parts of epoxy resin, 25 parts of epoxy acrylic resin, 11 parts of epoxy curing agent D230, 3 parts of N,N-dimethylbenzylamine, and 15 parts of propylene glycol.

[0090] Comparative Example 3: The nitrogen-doped carbon nanodots are not modified with branched polyethyleneimine, and the rest is the same as Example 1:

[0091] Step 1: Preparation of epoxy acrylic resin:

[0092] Take 5g toluene and 5g butyl acetate, stir evenly, heat to 47°C, add 16g butyl acrylate, 10.5g styrene, 0.15g azobisisobutyronitrile, 5.8g allyl glycidyl ether, 3.2g POSS, stir evenly to obtain a mixed solution A; take 12.5g toluene and 12.5g butyl acetate, stir evenly, add one-third of the mixed solution A by mass, heat to 80°C, stir for 25min, dropwise add the remaining two-thirds of the mixed solution A and 0.16g of thioglycolic acid, keep warm for 4h, and rotary evaporate to obtain an epoxy acrylic resin;

[0093] Step 2: Preparation of nitrogen-doped carbon nanodots:

[0094] Take 1.2 g of monohydrated citric acid powder and 10 mL of deionized water, dissolve them by ultrasonication, add 355 μL of ethylenediamine liquid, react at 200 °C for 8 h, cool and dry to obtain nitrogen-doped carbon nanodots;

[0095] Step 3: Preparation of corrosion-resistant zinc oxide microcapsules:

[0096] Take 1.5g of sodium dodecyl sulfate, 150mL of anhydrous ethanol, and 450mL of deionized water, stir evenly to obtain a sodium dodecyl sulfate solution; take 0.5g of nitrogen-doped carbon nanodots, 0.7g of benzotriazole, 50mL of anhydrous ethanol, and 3.8g of cyclohexane, stir evenly to obtain a nitrogen-doped carbon nanodot solution; add the sodium dodecyl sulfate solution to the nitrogen-doped carbon nanodot solution, stir for 18min, and obtain a mixed solution; take 16.5g of zinc acetate dihydrate and 45mL of deionized water, stir evenly to obtain a zinc acetate solution, add the zinc acetate solution dropwise to the mixed solution at 16°C, stir for 1.2h, centrifuge, and wash to obtain corrosion-resistant zinc oxide microcapsules;

[0097] Step 4: Preparation of photosensitive selective ink:

[0098] Alkali-soluble acrylic resin, acetone, UV monomer (meth) acrylate isobornyl, photoinitiator p-phenyl benzophenone, pigment carbon black, corrosion-resistant zinc oxide microcapsules, dispersant polyethylene glycol, defoamer polyoxypropylene oxyethylene glycerol ether, and accelerator 2-ethylimidazole are mixed uniformly to obtain a mixture A; epoxy resin, epoxy acrylic resin, epoxy curing agent D230, N, N-dimethylbenzylamine, and propylene glycol are mixed uniformly to obtain a mixture B; the mixture A and the mixture B are mixed uniformly to obtain a photosensitive selective ink;

[0099] The mixture A comprises the following components, by weight: 65 parts of alkali-soluble acrylic resin, 22 parts of acetone, 12 parts of UV monomer, 12 parts of photoinitiator, 17 parts of pigment, 20 parts of corrosion-resistant zinc oxide microcapsules, 1.5 parts of dispersant, 0.15 parts of defoamer, and 2.5 parts of accelerator;

[0100] The mixture B includes the following components, by weight: 35 parts of epoxy resin, 25 parts of epoxy acrylic resin, 11 parts of epoxy curing agent D230, 3 parts of N,N-dimethylbenzylamine, and 15 parts of propylene glycol.

[0101] experiment:

[0102] The performance test was carried out using the photosensitive selective ink prepared in Examples 1-3 and Comparative Examples 1-3. A tinplate sheet of 50 mm × 50 mm × 2 mm was selected as a substrate, which was cleaned and dried. The photosensitive selective ink prepared in Examples 1-3 and Comparative Examples 1-3 was then coated on the substrate surface with a coating thickness of 100 μm. The sample was cured by ultraviolet light. The sample was then immersed in an ammonium nitrate solution with a mass fraction of 20% at a temperature of 75°C for 3 days. The surface of the sample was observed to characterize the corrosion resistance of the ink. The pencil hardness was tested with reference to GB / T6739-2022. The adhesion of the ink layer was tested with reference to GBT7707-2008. The data obtained are shown in the following table:

[0103]

[0104] Pencil hardness Adhesion Corrosion resistance Example 1 4H Ink layer shedding area is less than 1.0% Surface intact Example 2 4H Ink layer shedding area is less than 1.0% Surface intact Example 3 4H Ink layer shedding area is less than 1.0% Surface intact Comparative example 1 4H Ink layer shedding area is less than 1.0% Surface blistering Comparative example 2 4H Ink layer shedding area is less than 1.0% Surface blistering Comparative example 3 4H Ink layer shedding area is less than 1.0% Surface blistering

[0105] Conclusion: The pencil hardness of the ink prepared by the present invention can reach 4H, and the bonding fastness of the ink layer is high. In Comparative Example 1, epoxy acrylic resin is not added, and the corrosion resistance of the ink is slightly reduced. In Comparative Example 2, modified nitrogen-doped carbon dots are not added, and the corrosion resistance of the ink is poor. In Comparative Example 3, the nitrogen-doped carbon dots are not modified with branched polyethyleneimine, and the corrosion resistance of the ink is reduced. Examples 1-3 of the present invention use branched polyethyleneimine to modify the nitrogen-doped nanodots, so that a large number of amino groups are grafted on the surface of the modified nitrogen-doped nanodots. The amino groups can react with the epoxy groups on the epoxy resin and the epoxy acrylic resin, so that the corrosion-resistant zinc oxide microcapsules are better dispersed in the ink, not easy to agglomerate, and the corrosion resistance of the ink is improved.

[0106] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a photosensitive selective ink, characterized in that: The following steps are involved: Step 1: Take toluene and butyl acetate, stir evenly, heat to 45-50°C, add butyl acrylate, styrene, azobisisobutyronitrile, allyl glycidyl ether, POSS, stir evenly to obtain a mixed solution A; take toluene and butyl acetate, stir evenly, add one-third of the mixed solution A by mass, heat to 80°C, stir for 20-30min, dropwise add the remaining two-thirds of the mixed solution A and thioglycolic acid, keep warm for 4-4.5h, and rotary evaporate to obtain epoxy acrylic resin; Step 2: taking an alkali-soluble acrylic resin, acetone, UV monomer, photoinitiator, pigment, corrosion-resistant zinc oxide microcapsule, dispersant, defoamer, and accelerator, and mixing them uniformly to obtain a mixture A; Step 3: Take epoxy resin, epoxy acrylic resin, epoxy curing agent, N, N-dimethylbenzylamine, and propylene glycol, mix them evenly to obtain a mixture B; Step 4: Evenly mix the mixture A and the mixture B to obtain a photosensitive selective ink; Take sodium dodecyl sulfate, anhydrous ethanol and deionized water, stir evenly to obtain a sodium dodecyl sulfate solution; take modified nitrogen-doped carbon nanodots, benzotriazole, anhydrous ethanol and cyclohexane, stir evenly to obtain a modified nitrogen-doped carbon nanodot solution; add the sodium dodecyl sulfate solution to the modified nitrogen-doped carbon nanodot solution, stir for 15-20 minutes, and obtain a mixed solution; take zinc acetate dihydrate and deionized water, stir evenly to obtain a zinc acetate solution, add the zinc acetate solution dropwise to the mixed solution at 15-17°C, stir for 1-1.5 hours, centrifuge and wash, and obtain corrosion-resistant zinc oxide microcapsules; Take nitrogen-doped carbon nanodots and deionized water, mix them evenly, add branched polyethyleneimine, stir at 60-65° C. for 100-120 min, and dry to obtain modified nitrogen-doped carbon nanodots.

2. The method for preparing a photosensitive selective ink according to claim 1, characterized in that: The preparation method of the nitrogen-doped carbon nanodots is as follows: 1.2 g of monohydrated citric acid powder and 10 mL of deionized water are taken, ultrasonically dissolved, 355 μL of ethylenediamine liquid is added, reacted at 200° C. for 7.5-8.5 h, cooled, and dried to obtain nitrogen-doped carbon nanodots.

3. The method for preparing a photosensitive selective ink according to claim 1, characterized in that: The mass ratio of the nitrogen-doped carbon nanodots, branched polyethyleneimine and deionized water is 0.5:(2-3):

10.

4. The method for preparing a photosensitive selective ink according to claim 1, characterized in that: The mixture A comprises the following components, by weight: 60-70 parts of alkali-soluble acrylic resin, 20-25 parts of acetone, 10-15 parts of UV monomer, 8-15 parts of photoinitiator, 15-20 parts of pigment, 15-25 parts of corrosion-resistant zinc oxide microcapsules, 1-2 parts of dispersant, 0.1-0.2 parts of defoamer, and 2-3 parts of accelerator.

5. The method for preparing a photosensitive selective ink according to claim 1, characterized in that: The mixture B comprises the following components, by weight: 30-40 parts of epoxy resin, 20-30 parts of epoxy acrylic resin, 10-12 parts of epoxy curing agent, 2-5 parts of N,N-dimethylbenzylamine, and 12-20 parts of propylene glycol.

6. The method for preparing a photosensitive selective ink according to claim 1, characterized in that: The UV monomer is any one or more of hydroxyethyl (meth)acrylate, isobornyl (meth)acrylate, diethylene glycol diacrylate, hexanediol diacrylate, trimethylol triacrylate, pentaerythritol triacrylate, and dipentaerythritol pentaacrylate; The photoinitiator is any one or more of benzophenone, p-phenylbenzophenone, isopropylthioxanthone, and 1-hydroxycyclohexyl phenyl ketone; The pigment includes one or more of carbon black, iron blue, ultramarine blue, phthalocyanine blue, titanium dioxide, and bismuth yellow; The dispersant includes any one or more of polyethylene glycol, polyacrylate, and sodium oleate; The defoaming agent includes any one or more of polydimethylsiloxane and polyoxypropylene oxyethylene glycerol ether; The accelerator includes any one or more of 2-methylimidazole, 2-ethylimidazole, and 2-ethyl-4-methylimidazole.

7. A photosensitive selective ink prepared according to the method for preparing a photosensitive selective ink according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Light-sensitive ink and preparation method and application thereof

    CN107177231A

  • Nitrogen-doped carbon dot@zinc oxide microcapsule and preparation method thereof

    CN110302822A